American College of Cardiology/European Society of Cardiology Joint Symposium on Lipids - Vinall, Maria (MD Conference Express, 2008)
When the results of the Investigation of Lipid Level Management Using Coronary Ultrasound to Assess Reduction of Atherosclerosis by CETP Inhibition and HDL Elevation [ILLUSTRATE] trial [Nissen SJ et al. N Engl J Med 2007] called into question the efficacy of the cholesteryl ester transfer protein (CETP) inhibitor torcetrapib, many thought it signaled the end of the pursuit of these compounds for the treatment of dyslipidemia. This article discusses new data from ILLUSTRATE, which provide hope for the future of CETP inhibitors.